Impact of International Student Enrollment on US Gross Domestic Product - Dr. Abhijeet Bhattacharya (International Journal of Engineering and Management Research, 2020)
The goal of this paper is to analyze the impact of international student enrollments on the US real gross domestic product. It is hypothesized that an increase in international student enrollment tends to have a positive impact on US real gross domestic product. It is also hypothesized that an increase in economic impact of international students has a positive impact on the US real gross domestic product. A regression model is formulated that consists of percentage increase in real gross domestic product (economic growth rate) as the dependent variable. The independent variables used in the regression model are annual percentage increase in international student enrollments in the US and the annual percentage increase in economic impact of the international students in the US. Data is collected from 2009 to 2015 from the Bureau of Economic Analysis and NAFSA. It is important to analyze the rationale as to why highly skilled immigration is vital for promotion of entrepreneurship and innovation in the US economy. The current administration is trying to undermine the positive impact of highly skilled immigration on the US economy. The issue is critically important in the prevailing political climate in the US economy. An attempt is also made to formulate strategies that would help in mitigating negative outcomes such as potential declines in revenues for US universities as well as decline in research and grant funding that would arise due to decrease in international student enrolments.